Mentor-Based Learning to Enhance SMAW Welding Outcomes in Vocational Entrepreneurship Education - Gibran Raja Ichi Abubakar; Widiyanti Widiyanti (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Vocational education must ensure that students acquire not only technical competence but also the confidence and critical thinking needed for real-world tasks. This study investigates the effectiveness of a mentor-based instructional model in enhancing student performance in Shielded Metal Arc Welding (SMAW) practices within the subject of Creativity, Innovation, and Entrepreneurship at SMK Negeri 1 Singosari, Indonesia. Using a descriptive quantitative approach, data were collected from 70 eleventh-grade mechanical engineering students through structured performance assessments and Likert-scale questionnaires. The results show a high average performance score of 84.04 with a standard deviation of 3.18, where 89% of students were categorized as “High” and 11% as “Very High.” Performance scores increased progressively across assessment stages, and students reported improved confidence, motivation, and procedural accuracy. These findings suggest that structured mentoring significantly supports technical mastery, reduces skill disparities, and cultivates reflective learning habits. It is concluded that mentor-guided learning should be integrated more widely in vocational curricula. It is also recommended that future research explore the long-term impact of mentoring on work readiness, creativity, and entrepreneurial mindset across other technical fields.